Aspects of research to reduce the effect of trypanosomiasis on animal production in Africa - Trail, J.C.M.; D'Ieteren, G.D.M. (Institute of Agricultural Research, 1989)
A paper dealing with research conducted to reduce the effect of trypanosomiasis on animal production in Africa. Looks into the African Trypanotolerant livestock Network and discusses the exploitation of trypanotolerant breeds, trypanosome prevalence and animal performance. Also examines specific research inputs.